Piety and Tolerance in Thai Society: Exploring Multicultural Coexistence at Phatnawitya School - Nuruzzaman, Muhammad Adib; Ridwan, Auliya; Safriani, Afida; Ha’sa, Wan Anita (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
Thailand's society, rich in ethnic and religious diversity, underscores the importance of piety and tolerance in maintaining social harmony. This study examines the practices of instilling the values of piety and tolerance at Phatnawitya School, through their integration into the curriculum and school activities. It also explores the challenges faced in creating an environment that values diversity in both the school and the broader multicultural community. Utilizing a qualitative approach and case study methodology, this research gathers both primary and secondary data. The findings indicate that Islamic education at Phatnawitya School plays a crucial role in nurturing piety and tolerance among students through the Islamic religious curriculum, extracurricular activities, and student empowerment programs. This educational approach has successfully fostered an environment conducive to student social development. The conclusion of this study highlights the role of Islamic education as an effective tool in shaping students with harmonious and tolerant characters, as well as contributing to the development of a multicultural society.